Competitiveness of the Baking Industry in the Northern Province of Sri Lanka - Umashankar, K.; Jathukulan, S. (Sri Lanka Agricultural Economics Association, 2016)
As far as Sri Lanka is concerned the SME sector is the backbone of the nation. It contributes to the development of the country on a massive scale while opening up avenues for employment for the community at large. Albeit there are plenty of avenues for the growth of SMEs in the Island nation. With this assessment of the SME in mind, the researchers have taken effort to study the functional aspects of the bread making industry in Northern Province of Sri Lanka which undeniably has become an integrate part of the diet of the Sri Lankan polity. From this information, having collected randomly 151 samples, researchers began primary questionnaire survey. The final data obtained were analyzed through three methodological frameworks namely Ordinary Least-Square Regression Analysis, Business Model canvas and Business Model Environment. The results revealed that the experience of the entrepreneur, numbers of employees, access to credit, yeas of running show significant results in this analysis. The business external factors such as Market forces, Industry forces, key trends and macroeconomic forces were elaborately discussed and constraints encountered. in the study of external forces such as high competition with the big time players of other provinces, marketing constraints, government policy, financial constraints, lack of technology and economic infrastructure, and lack of quality control requirements were identified and had to be rectified through possible practical solutions and by the development of baking SME sector.
Keywords: Small and Medium Scale Enterprise; Business Model Canvas; Business External Forces; Ordinary Least-square